TINJAUAN YURIDIS PERTANGGUNG JAWABAN RUMAH SAKIT ATAS KE IKUT SERTAAN DALAM PROGRAM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN - Ariawan Gunadi; Ida Nursida (Faculty of Law - Tarumanagara University, 2019)
The Social Security Administering Body (BPJS) is a public legal entity formed to organize a social security program. Social Security Agency can alleviate the burden of society in obtaining health services in hospitals or clinics. This is in accordance with Article 5 Paragraph (1) and Paragraph (2) of Law No.36 Year 2009 on Health. and Article 47 Regulation of Health BPJS No.1 Year 2014 on the implementation of Health Insurance. As an insurance company BPJS health ensures the implementation of health programsHospitals and Clinics as health service providers in demand by the government to play an active role in providing good health services to the community according to its function, in accordance with Law Number 44 Year 2009 on Hospital. But even if the hospital or health service supports the social health insurance program or BPJS is proved by the poster that the Hospital or Clinic receive BPJS patients, does not mean that the service received by the community is in line with expectations.